Implementasi Sistem Monitoring pada Bunga Anggrek Menggunakan Arduino dengan Aplikasi Berbasis Website - Wandhana, Gede Krisnawa Sandhya; Agung Gede Arya Kadyanan, I Gusti (Jurnal Nasional Teknologi Informasi dan Aplikasnya; Vol 1 No 3 (2023): JNATIA Vol. 1, No. 3, Mei 2023DO - 10.24843/JNATIA.2023.v01.i03.p09, 2023)
This article will focus on implementing an orchid plant monitoring system using Arduino in a web-based application. The purpose of this system is to monitor important environmental parameters such as temperature, humidity and soil moisture in real time. By collecting data from orchid plants using sensors, the system enables continuous measurement and analysis of these parameters. Collected data is processed and stored by the Arduino, which acts as the central control unit. A web-based application serves as the user interface, allowing remote access and visualization of monitoring data. Implementation of this system provides a practical solution for improving orchid cultivation through accurate and easily accessible monitoring of key parameters. This allows researchers and hobbyists to closely monitor growing conditions and make informed decisions based on the data collected. By maintaining optimal environmental conditions, the system contributes to improved growth, increased yields and successful cultivation of orchid plants. The combination of an Arduino and a web-based application provides an efficient and easy-to-use solution for orchid plant monitoring and management for better results in your orchid cultivation practice.